PENGEMBANGAN PANDUAN PRAKTIKUM VIRTUAL DENGAN MODEL INKUIRI TERBUKA PADA MATERI FLUIDA DINAMIS - Ratela, Jansi (Charm Sains: Jurnal Pendidikan Fisika, 2020)
This research is a development research (R & D) with a 4D Model which aims to develop a learning guide based on virtual practicum material with dynamic fluid concepts. This study used an open inquiry learning model which was tested on 8 students as a limited trial and 30 students as a field trial at SMA Negeri 1 Tenga Minahasa Selatan using the 2013 curriculum. The research instrumentused was the feasibility test of a guide consisting of a checklist that contained assessment by material expert lecturers and media expert lecturers and student responses about the use of virtual practicum guides. In this study, using the LKS assessment instrument to assess the effectiveness of the learning guide in virtual practicum. Data analysis techniques include criteria for interpretation and data processing. The results showed that 1. Open inquiry-based practicum guide that has been validated by a team of experts and the students' responses get good scores. 2. The scores and achievement scores obtained by students in the small group test and the large group test have been completed according to the KKM value so that it can be concluded that the effectiveness of the learning device being tested is feasible to use.